High Serum Uric Acid Was a Risk Factor for Incident Asthma: An Open Cohort Study - Wang H; Jia Y; Yi M; Li Y; Chen O (Dove Medical Press, 2020)
Haixia Wang, Yuanmin Jia, Mo Yi, Yizhang Li, Ou Chen School of Nursing, Cheeloo College of Medicine, Shandong University, Jinan 250012, Shandong, People’s Republic of ChinaCorrespondence: Ou ChenSchool of Nursing, Cheeloo College of Medicine, Shandong University, Jinan 250012, Shandong, People’s Republic of ChinaTel +86 15990991181Email chenou@sdu.edu.cnBackground: Several cross-sectional studies have suggested an association between SUA and asthma. However, few studies have investigated this relationship longitudinally. Although SUA is an independent risk factor for chronic kidney disease and cardiovascular diseases, its contribution to incident asthma remains uncertain.Objective: To determine whether a high SUA was a risk factor for adult incident asthma.Methods: By using health care data from the Shandong multicenter health check-up, 76,369 participants, aged 20 to 79 years, were identiﬁed who had an SUA determination with a mean follow-up period of 3.73± 2.21 years. Multivariate modeling employed Cox proportional hazards models to verify the association between SUA and incident asthma by adjusting age, BMI, smoking habits, drinking habits, and asthma-like diseases.Results: A total of 51,389 individuals were included in the analysis. Cut-off values of SUA able to discriminate asthma status were identified by means of maximally selected rank statistics in the whole participants (≥ 376.80umol/L), women (≥ 314.45umol/L), and men (≥ 376.80umol/L). Multivariate Cox regression analyses adjusted for covariates (age, body mass index (BMI), smoking habit, drinking habit, and asthma-like disease) identified an independent association between SUA and incident asthma in the whole participants (hazard ratio (HR) 2.92, 95% confidence intervals (CI), 1.76– 4.48, P=0.00) and men (HR 3.02, 95% CI 1.70– 5.39, P=0.00), but not in women.Conclusion: The results of the current study confirmed that high SUA was an independent risk factor for incident asthma after adjustment of potential covariates and suggested that a cut-off value related to incident asthma could be identified only in men.Keywords: cut-off value, asthma, gender, serum uric acid, risk factor